Macroeconomic Variables and Gross Domestic Product: Evidence from Sri Lanka - Kengatharan, L.; Jeyan Suganya, D.F.; Yogendrarajah, R. (International Journal of Accounting & Business Finance Vol.7 (Special) pp. 17-30, 2021)
The main objective of the study is to investigate the empirical relationship between macroeconomic variables and real gross domestic product (GDP) in Sri Lanka. Exchange rate, government spending, interest rate, money supply and unemployment rate were considered as selected macroeconomic variables. real GDP was considered as a dependent variable. The current study used annual time series data over the period from 1990 to 2019 which were collected from the annual reports of the Central Bank of Sri Lanka. Stationary of the data was tested using the Augmented Dickey-Fuller test. Johansen co-integration rank test, max Eigen value test, Vector Error Correction along with Wald causality test were used to estimate the relationship between macroeconomic variables and GDP. At the 5% level of significance, the co-integration rank test and max Eigen value test revealed that there are four co-integration equations exist in this study. Therefore, it was concluded that selected macroeconomic variables have long run impact on GDP. Likewise VEC and Wald test revealed that the all the selected macroeconomic variables causes GDP in the short run. The results support the theoretical prediction that macroeconomic variables would play an active role in GDP. The study, therefore, concludes that macroeconomic variables are driving GDP in Sri Lanka. Thus, growth-oriented macroeconomic policies should be established for protecting poor people in the country.
Keywords: Macroeconomic variables; GDP; Vector Error Correction Model; Sri Lanka